PEMISAHAN TAIWAN DARI NEGARA CHINA DARATAN MELALUI REFERENDUM RAKYAT TAIWAN - Ridharmagista, Syah Okka; Setya Putra, Pamungkas (Jurnal Ilmiah Wahana Pendidikan, 2023)
ABSTRACT The dynamic relationship between China and Taiwan is still unresolved at this time, starting from the civil war between the Communist Party and the National Party which has yet to end fighting for the disintegration of Taiwan from the bosom of China. What was then rejected by President Tsai Ing-Wen of Taiwan regarding the One China policy (One Policy Of China) which continued to shout independence for Taiwanese in any way. In fact, President Xi Jinping held back to keep Taiwan in the lap of China's sovereignty. The purpose of this research is to see how the struggle of the Taiwanese people in shouting for their independence by referendum is seen from the consensus prevailing in the international community by analyzing the rights contained in the UN Charter and International Law. This research uses the juridical-normative method by obtaining secondary data from research libraries and literacy about the legal protection of Taiwanese citizens in the form of scientific journals and scientific articles. In this research, it is hoped that the transparency of international legal transparency towards Taiwanese citizens, which until now has no clear identity in the international world. Keyword : Disintegration, One Policy China, Referendum